Protein-chip for autoantibodies profile detection - Wang, Guoqiang; Gao, Xueqin; Han, Jinxiang; Pan, Jihong; Huang, Hainan (Shengwu gongcheng xuebao, 2008)
We selected 12 antigens corresponding to commonly used autoantibodies in clinical practice to prepare antigen microarray. We chose NBT/BCIP color reaction as the end detection strategy to develop a new autoantibody protein chip detection system. Using this system, we optimized the best spotting solution, spotting concentration of the 12 antigens and the dilution of serum. We prepared a protein chip that could detect 12 autoantibodies simultaneously using the optimized antigen concentration. We established a new method to determine the cutoff of each autoantibodies by evaluation of 678 positive and 120 negative serum of clinical sample. We also evaluated the sensitivity and specificity of our new detection system. The optimal spotting solution was 0.1% TBST, the dilution of serum was 1:4 and the best spotting concentration of the 12 antigens were ANA 520 microg/mL, Ro-60/SSa 465 microg/mL, La/SSb 530 microg/mL, Jo-1 530 microg/mL, Scl-70 525 microg/mL, Sm 520 microg/mL, Ro-52/SSa 615 microg/mL, RF 340 microg/m